Alzheimer's disease: classification and diagnosis criteria - Katarzyna Swakowska; Anna Staniszewska (Kazimierz Wielki University, 2021)
<p class="MsoNormal" style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" align="justify">In recent  years, the intensity of population aging has increased and the incidence of senile diseases, including dementia, has significantly increased. With the aging of populations in Europe, knowledge about the detection and diagnosis of dementia has increased in the last decade. Due to the increase in the number of patients, new therapies and precise diagnostic criteria have been introduced, contributing to faster diagnosis of the disease. Alzheimer's disease (AD) is the biggest cause of dementia in old age. It is characterized by progressive cognitive deficits, especially memory, and disorders such as: apathy, agitation and psychotic symptoms. Alzhaimer's disease is a degenerative brain disease caused by the deposition of pathological B-amyloid protein tau and alpha-synuclein in the brain, causing atrophy of neurons and their connections. The basis for diagnosis of dementia in the course of Alzheimer's disease are ICD-10 or DSM-IV criteria. The clinical course and symptoms in the course of AD are defined by the Global <span style="font-family: 'Times New Roman'; line-height: 150%; color: #202124; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Deterioration Scale (GDS), the scale also determines the stage of the disease. Acetylcholinesterase inhibitor drugs and memantine are used to treat the symptoms of Alzheimer's disease. Prompt diagnosis and treatment significantly delays the progression of the disease and helps to prolong normal functioning of the patient.